Evaluation of long-term hard tissue remodelling after skeletal class III orthognathic surgery: a systematic review. Issue 1 (January 2020) - Gaitán Romero, L.; Mulier, D.; Orhan, K.; Shujaat, S.; Shaheen, E.; Willems, G.; Politis, C.; Jacobs, R.
Abstract: This systematic review was performed to investigate the long-term hard tissue stability in orthognathic surgery patients with skeletal class III malocclusion. A literature search was conducted using the Embase, Cochrane Central, Web of Science, and PubMed databases, yielding 3690 articles published up to June 2018. Nine articles met the inclusion criteria; these reported skeletal changes in 886 patients with between 5 and 12.7 years of follow-up. Risk of bias was assessed according to the Cochrane Handbook. Results showed variations in stability based on age, facial pattern, surgical procedure, and fixation type. Young patients showed a greater increase in mandibular length and higher A-point stability after bimaxillary surgery than older patients. Dolichofacial patients showed skeletal relapse with a facial clockwise rotation, whereas counterclockwise rotation was observed in brachyfacial patients. Single mandibular setback surgery was linked to stability loss with decreased mandibular ramus and gonion angle; meanwhile, genioplasty fell into the highly stable surgery category. The hyoid bone relapsed significantly postero-inferiorly, which correlated with suprahyoid muscle changes but little to no mandibular position changes. Fixation with monocortical miniplates showed higher patient satisfaction and better stability compared to bicortical screw fixation. These conclusions should be regarded with caution because of the lack of current evidence from three-dimensional imaging.